Commercial farmers’ strategies to control water resources in South Africa: an empirical view of reform - Méndez Barrientos, L.E.; Kemerink, J.S.; Wester, P.; Molle, Francois (Informa UK Limited, 2018)
This article shows how large-scale commercial farmers, individually and collectively, are responding to land and water reform processes in the Thukela River basin, KwaZulu-Natal, South Africa. With a high degree of innovative agency, commercial farmers have effectively executed four strategies, enabling them to adapt and use their access to resources to neutralize multiple water reform efforts that once promised to be catalysts for inclusive change in the post-apartheid era. It is likely that policy alone will not facilitate the envisioned transformation, if local practices are not sufficiently understood and anticipated by the governmental officials charged with the implementation of water reform processes.